2020
DOI: 10.5194/acp-20-13929-2020
|View full text |Cite
|
Sign up to set email alerts
|

Baffin Bay sea ice extent and synoptic moisture transport drive water vapor isotope (<i>δ</i><sup>18</sup>O, <i>δ</i><sup>2</sup>H, and deuterium excess) variability in coastal northwest Greenland

Abstract: Abstract. At Thule Air Base on the coast of Baffin Bay (76.51∘ N, 68.74∘ W), we continuously measured water vapor isotopes (δ18O, δ2H) at a high frequency (1 s−1) from August 2017 through August 2019. Our resulting record, including derived deuterium excess (dxs) values, allows an analysis of isotopic–meteorological relationships at an unprecedented level of detail and duration for high Arctic Greenland. We examine isotopic variability across multiple temporal scales from daily to interannual, revealing that i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 129 publications
(202 reference statements)
2
4
0
Order By: Relevance
“…Significant positive relations were also observed in Russia at Labytnangi (0.58 / • C, r 2 = 0.62) and Tura (0.53 / • C, r 2 = 0.57), and are similar to a regional Siberian slope of 0.50 / • C that was proposed by Kostrova et al (2020). Toolik Lake in Alaska (0.31 / relationships, albeit relatively weak, and these slopes are similar to previously reported regional values for Alaska and Greenland Bailey et al, 2018;Akers et al, 2020). Across all sites, the steepest temperature-δ 18 O slopes (between 0.93 and 0.75 / • C) were observed at the continental stations-a pattern also observed across the United States (Vachon et al, 2010;Akers et al, 2017), Europe (Rozanski et al, 1982), and Antarctica (Peel and Mulvaney, 1992).…”
Section: Meteorological Factorssupporting
confidence: 89%
See 1 more Smart Citation
“…Significant positive relations were also observed in Russia at Labytnangi (0.58 / • C, r 2 = 0.62) and Tura (0.53 / • C, r 2 = 0.57), and are similar to a regional Siberian slope of 0.50 / • C that was proposed by Kostrova et al (2020). Toolik Lake in Alaska (0.31 / relationships, albeit relatively weak, and these slopes are similar to previously reported regional values for Alaska and Greenland Bailey et al, 2018;Akers et al, 2020). Across all sites, the steepest temperature-δ 18 O slopes (between 0.93 and 0.75 / • C) were observed at the continental stations-a pattern also observed across the United States (Vachon et al, 2010;Akers et al, 2017), Europe (Rozanski et al, 1982), and Antarctica (Peel and Mulvaney, 1992).…”
Section: Meteorological Factorssupporting
confidence: 89%
“…Our data indicate that precipitation associated with these northnorthwesterly air flows were characterized by anomalously low δ 18 O and high d-excess values, such as at Thule in northwest Greenland (Figure 2). A recent study also observed a similar relation between the NAO and atmospheric water vapor isotopes measured at Thule between 2017 and 2019, whereby NAO+ circulation phases suppressed southerly flow into Thule, leading to cooler SATs and lower δ-values and higher d-excess (Akers et al, 2020). Additionally, approximately 61% of Toolik trajectories started from central Arctic regions, with precipitation characterized by anomalously low δ 18 O and high dexcess (Figure 5), with the lowest measured δ 18 O value reaching −28.5 (28 Aug) that derived from the central Arctic basin and passed over the Chukchi Sea.…”
Section: Out Of the Arcticsupporting
confidence: 60%
“…However, the existing models are not suited to capture key processes causing isotope evolution in Arctic seasonal snow layers: vapor diffusion from soil to snowpack, and isotope fractionation during sublimation. A way forward could be the introduction of isotope simulation routines into physically based snow models already characterizing the water fluxes (vapor flow, sublimation) and snow densification [103,107,108].…”
Section: Uncertainties and Wider Implicationsmentioning
confidence: 99%
“…Due to the ability of stable water isotopes to characterize the origin of water [48] and to the differences in water vapor isotopic compositions from different sources, stable isotope technology has gradually become a common method for tracing water vapor sources. Investigations by some scholars have found that δ 18 O and d-excess in precipitation can be used to determine the origin of water vapor [20,23,49] Affected by various factors such as near-surface meteorological conditions, the LMWL varies from region to region. According to the least square method, the LMWL of the study area and each sampling station is obtained.…”
Section: Water Vapor Source Information Indicated By δ 18 O and D-excessmentioning
confidence: 99%